Efficiency Research With Total Factor Productivity and Determination of Improvement Targets - Bilişik, Murat Taha; Özkaya Elibol, Gülizar (My University, 2017)
Purpose - In today's competitive world, when financial crises and economic stagnation are experienced, the effective and efficient use of resources has become an important and necessary condition for companies and country economies. The iron-steel industry, which provides a great deal to the country's economies, also provides raw materials to a large number of industries. In the iron-steel industry, where our country has limited resources and high dependency on external sources, it is necessary to determine whether the resources are used correctly to evaluate the efficiency and productivity and to determine the appropriate improvement targets. Methodology – In this study, the activities of 9 iron and steel companies listed in Istanbul stock market and operating in the Turkish iron and steel industry have been examined using output oriented Data Envelopment Analysis (DEA) which is a non-parametric approach and Malmquist productivity index (MPI). In the study, 3 input factors have been number of employees, fixed assets and current assets. On the other hand, 2 output factors have been revenue and gross profit . The required data sets were obtained from 2014 and 2015 financial statements of the relevant companies. Findings – Technical efficiencies, pure efficiencies, scale efficiencies and Malmquist indexes for each company have been found. According to the results obtained, decision making units which are efficient and inefficient were determined. By the way, the reasons for Malmquist Productivity Index, in terms of technical change and technological cahange have been explained. Conclusion – Iron-steel companies determined to be unproductive may use these results to find out the detailed reasons preventing them to be productive. Since activities are directly proportional to the use of resources, organizations need to reduce input or take measures to increase their output. Increasing the production of high value added products or increasing the production can increase the income. Especially in view of stainless steel, special steel and seamless pipe products, which are insufficient in Turkey, an increase should have been in export and imports. With plans and strategies to be implemented in this way, both the cost of inputs can be reduced and the output can be increased.
Keywords: Iron-steel industry; data envelopment analysis (DEA); malmquist productivity index (MPI); efficiency; productivity